The Harp of the Soul: Neuroacoustic and Psycho-spiritual Mechanisms of the Ethiopian Begena as a Therapeutic Modality for Grief, Anxiety, and Spiritual Dryness - Kassahun Desealegn Asfaw; Nigussie Mamushet Degeif; Belay Sitotaw Goshu; Arifulhak Aceh (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
Grief, anxiety, and spiritual dryness represent interconnected forms of human suffering with limited culturally grounded interventions. The Begena a 10-stringed Ethiopian lyre associated with King David has been used for centuries in Ethiopian Orthodox Tewahido Church meditation as "food for the soul." This paper advances the thesis that the Begena constitutes a neuroacoustic and psycho-spiritual intervention, not merely music, for grief, anxiety, and spiritual dryness. An integrative review synthesizing biblical scholarship (1 Samuel 16:14–23), Ethiopian Orthodox liturgical tradition, Polyvagal Theory, neuroacoustic research on low-frequency resonance, resonance, electroencephalography (EEG) studies of alpha/theta oscillations, and psycho-spiritual theories of holding environments and meaning-making. The Begena produces low-frequency resonance (80–250 Hz) overlapping vagus nerve optimal band (100–200 Hz), inducing parasympathetic tone (HRV +73%) and theta/alpha enhancement (4–12 Hz, +140–175%). Inter-note silence (≥3 seconds) decouples default mode network activity by 65%, reducing rumination. Psycho-spiritually, the instrument provides non-verbal containment for grief, companions’ spiritual dryness, and facilitates metanoia (repentance) as cognitive reappraisal. The Begena is a dual-mechanism therapeutic modality meriting clinical investigation. Pilot randomized controlled trial (RCT) comparing Begena listening to white noise and silence for prolonged grief disorder.